(untitled) (Journal of Applied Learning and Teaching, 2026)
This paper addresses a dual challenge in higher education: making HyFlex implementation more sustainable whilst overcoming terminology-based resistance that prevents educators from recognising intelligent tools as pedagogical supports. Between October 2024 and July 2025, the University of Southern Queensland participated as the sole non-European institution among 17 providers in the Jisc Beyond Blended pilot, simultaneously running an internal HyFlex-Beyond Blended initiative across two trimesters. Drawing on a Scholarship of Teaching and Learning framework and critical reflective practice, this study examines the integration of intelligent tools across synchronous and asynchronous HyFlex modalities. Insights from practice suggest that framing tools by pedagogical function rather than technological label reduced adoption resistance and supported HyFlex principles of choice, flat learning, and accessibility. Purpose-built AI agents supported learning design, automated content creation reduced educator workload, and conversational AI enhanced asynchronous engagement. However, infrastructure limitations, a flexibility-engagement paradox, and a lack of student feedback constrain claims. Three theoretical contributions are offered: framing affects intelligent tool adoption; AI capabilities can operationalise HyFlex principles that have been theoretically sound but practically challenging; and critical reflective practice can generate valid scholarly insights from institutional pilots. Implications include pedagogical framing in change management, phased implementation, and embedding tools within existing workflows.